2020
DOI: 10.1108/jabs-08-2019-0261
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor support, work engagement and turnover intentions: evidence from Indian call centres

Abstract: Purpose This paper aims to examine the relationship between supervisor support, work engagement and turnover intentions with work engagement playing the role of a mediator. Design/methodology/approach Data from 386 Indian call centre employees through questionnaire survey was collected. A variety of statistical tools such as confirmatory factor analysis, Sobel test and descriptive statistics were used for examining the relationship. Findings From this study, it was found that work engagement partially medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 63 publications
2
41
0
3
Order By: Relevance
“…Servant leadership is known to provide followers with emotional support, feedback or resources and is, therefore, conceptually related to a leader’s use of emotions. That study’s outcome is consistent with the results of a simulation study in which a leader’s positive affect was strongly associated with follower intrinsic motivation (Kraiger et al , 1989; Pattnaik and Panda, 2020).…”
Section: Perceived Leader Use Of Emotions Follower Need Satisfaction ...supporting
confidence: 87%
“…Servant leadership is known to provide followers with emotional support, feedback or resources and is, therefore, conceptually related to a leader’s use of emotions. That study’s outcome is consistent with the results of a simulation study in which a leader’s positive affect was strongly associated with follower intrinsic motivation (Kraiger et al , 1989; Pattnaik and Panda, 2020).…”
Section: Perceived Leader Use Of Emotions Follower Need Satisfaction ...supporting
confidence: 87%
“…When job demands increase, employees mobilises the physiological and psychological costs such as increased sympathetic activity, fatigue and irritability to maintain the performance level (Schaufeli et al, 2009). Continuous mobilisation of these compensatory efforts may lead to negative emotional and job outcome such as turnover intentions, burnout, low job satisfaction (Pattnaik and Panda, 2020), chronic exhaustion and physical health problems (Bakker and Demerouti, 2018).…”
Section: Job Demand-resources Modelmentioning
confidence: 99%
“…In this instance, the JD-R model provides an explanatory framework to clarify how employee perceptions of workplace digitalisation are linked to employee engagement. The JD-R model describes that job demands and job resources could predict employee behaviour (such as employee engagement) (Imperatori, 2017;Pattnaik and Panda, 2020;Schaufeli and Bakker, 2004). Job demands strain employees' energy, increases stress, burnout and lower engagement, but job resources provide employees with the basic needs and motivation to employees to focus their energetic and cognitive resources at work, thus, positive to employee engagement (Pattnaik and Panda, 2020).…”
Section: Relationship Between Workplace Digitalisation and Employee Engagementmentioning
confidence: 99%
“…A study by Pattnaik and Panda (2020) reported that high supervisor support led to high-quality relationships between supervisors and their employees, which, in turn, influenced the engagement levels among Indian call center employees. Applying the same logic advanced by SET, employees with high work engagement rewarded the organization with reduced levels of intention to leave the organization (Saks, 2019).…”
Section: Workplace Social Support and Work Engagementmentioning
confidence: 99%